Breeding biology of Eared Quetzals in the Sierra Madre Occidental, Mexico - González Rojas, José Ignacio; Cruz Nieto, Javier; Ruvalcaba Ortega, Irene; Cruz Nieto, Miguel A. (2008)
Eared Quetzals (Euptilotis neoxenus), a threatened species, are one of the least studied trogons in Mexico. We monitored 29 Eared Quetzal nests in the Chihuahuan portion of the Sierra Madre Occidental from 1998 to 2003. All nests were in tree cavities, and the mean tree and nest cavity heights (N = 14) were 16.9 ± 7.8 mand11.4 ±4.1m,respectively. The mean clutch size was 2.8 ± 0.9 eggs (N = 28), the incubation period lasted 22 d (N =1),andnestling periods ranged from 29 to 31 d (N = 5). Both adults incubated eggs and fed nestlings. Of 80 eggs, 70 hatched (87.5%) and 67 of 70 young fledged (95.7%). Twenty-five of 29 nests (86.2%) produced at least one fledgling. One nest was predated, and two failed when nest trees fell. Higher rates of nest predation have been reported for other species of trogons. However, fewer potential predators, such as snakes and mammals, are present in the Sierra Madre than in tropical zones where most trogon species occur. In addition, antipredator behaviors, including nestlings with calls resembling a snake and nests with an unpleasant odor, may contribute to the high nesting success. The main limiting factors for Eared Quetzals in the northern Chihuahua may be competition for cavities with other secondary cavity-nesters, and the failure of nests when snags fall.